WORK ENVIRONMENT FACTORS IN AFFECTING EMPLOYEE PERFORMANCE - Dermawan Perangin Angin; Marto Silalahi; Marthin Hutler Ambarita; Sudung Simatupang; Swendy Barus (Bajang Institute, 2021)
This study aims to determine the effect of the work environment on the performance of the employees of the Public Administration Section of the Pematangsiantar City Regional Secretariat, totaling 28 employees. For the results of the validity analysis, it was found that the results were valid and for reliability the results were reliable. For the results of normality, it is concluded that the data is normally distributed, with a coefficient of determination of 36% while the rest is influenced by other factors and the correlation value of the variables is included in the strong category. The regression equation shows positive equation results and the hypothesis results provide an answer that partially, the work environment has a positive and significant effect on employee performance, because the work environment is the most important factor in achieving employee performance.